1996
DOI: 10.1121/1.414863
|View full text |Cite
|
Sign up to set email alerts
|

Sources and effects of low-frequency noise

Abstract: The sources of human exposure to low-frequency noise and its effects are reviewed. Low-frequency noise is common as background noise in urban environments, and as an emission from many artificial sources: road vehicles, aircraft, industrial machinery, artillery and mining explosions, and air movement machinery including wind turbines, compressors, and ventilation or air-conditioning units. The effects of low-frequency noise are of particular concern because of its pervasiveness due to numerous sources, efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
237
1
20

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(265 citation statements)
references
References 90 publications
7
237
1
20
Order By: Relevance
“…Persson and Bjorkman (1988) and Persson et al (1990) found that dB(A) underestimates the level of annoyance for low frequency noise. This, along with other related work implies that noise at low frequencies is considered more annoying by individuals (Broner, 1978;Berglund et al, 1996;Pawlaczyk-Luszczynska, 2010). Moreover, related research has also found that low frequency noise has a greater degree of 'unpleasantness' than noise in the A-weighted frequency bands (Inukai et al, 2000;Nakamura and Inukai, 1998).…”
Section: Introductionsupporting
confidence: 56%
“…Persson and Bjorkman (1988) and Persson et al (1990) found that dB(A) underestimates the level of annoyance for low frequency noise. This, along with other related work implies that noise at low frequencies is considered more annoying by individuals (Broner, 1978;Berglund et al, 1996;Pawlaczyk-Luszczynska, 2010). Moreover, related research has also found that low frequency noise has a greater degree of 'unpleasantness' than noise in the A-weighted frequency bands (Inukai et al, 2000;Nakamura and Inukai, 1998).…”
Section: Introductionsupporting
confidence: 56%
“…Noise pollution, especially low-frequency noise (20 to 100 Hz), is harmful to the human body, because of the resonance of audio frequency and the internal constituents, which can produce damage to internal organs (Berglund et al 1996). Noise pollution is also one of the most important environmental problems and is harmful to human health, as is exemplified by hearing loss and body lesions (Stansfeld and Matheson 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Infrasound noise is sensed by humans either by hearing and beyond-hearing way -by vibration receptors placed all over the body. The authors (Berglund, Hassemen, 1996;Leventhall et al, 2003; Pawlaczyk-Łuszczyńska, 1999) highlight that arduous impact of infrasound noise is characterised by symptoms such as exhaustion, discomfort, sleeplessness, impaired balance, psychomotor skills, and disruption (Jacobsen, 2001), including Dutch guidelines concerning permissible infrasound levels in rooms from outside sources. These guidelines describe the level of 85 dBG as maximum level suggested in most rooms.…”
Section: Introductionmentioning
confidence: 99%